Respuestas
Respuesta dada por:
1
Sabiendo que: Cos(2x)=1 - 2Sen²x
y que: sen²x=1-cos²x
entonces: 1 - 2Sen²x = 2 - 2 cos² (x)
1 - 2Sen²x = 2(1-cos²x)
1-2sen²x = 2sen²x
1 = 2sen²x+2sen²x
1 = 4sen²x
1/4 = sen²x
√(1/4) = senx
(i) Buscamos en tabla los valores del angulo donde sen es 1/2
senx = 1/2, entonces x=30°,150°
(ii) Buscamos en tabla los valores del angulo donde sen es -1/2
senx=-1/2, entonces x=210°,330°
conjunto solucion = {30,150,210,330} 0≤x≤360
y que: sen²x=1-cos²x
entonces: 1 - 2Sen²x = 2 - 2 cos² (x)
1 - 2Sen²x = 2(1-cos²x)
1-2sen²x = 2sen²x
1 = 2sen²x+2sen²x
1 = 4sen²x
1/4 = sen²x
√(1/4) = senx
(i) Buscamos en tabla los valores del angulo donde sen es 1/2
senx = 1/2, entonces x=30°,150°
(ii) Buscamos en tabla los valores del angulo donde sen es -1/2
senx=-1/2, entonces x=210°,330°
conjunto solucion = {30,150,210,330} 0≤x≤360
Adjuntos:
![](https://es-static.z-dn.net/files/da3/d36a6548a44723953caf3f81621e2f1e.png)
![](https://es-static.z-dn.net/files/d61/97663e079d12d1fb16abf3d637312fa5.png)
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años